EXPRESSION OF NON-LITERARY VOWELS IN PROBLEM TEXTS - Uralov Elyor Normanovich (Scholars Digest Publishing, 2024)
This article examines non-literary vowel sounds found in problematic texts and their connection with the thematic nature of the text. It provides substantiated concepts for determining the stages of analysis and determining their practical and theoretical solutions in accordance with the object of linguistic examination. It presents the basics of analyzing written and oral texts on various topics.
Keywords: vulgar vowels, problematic text, linguistic examination, identification analysis, diagnostic analysis, phonetic analysis, linguopragmatic analysis, phonoscopic examination.